Potential curve for a Helium dimer confined by prolate spheroidal boxes - Batael, Hugo de Oliveira [UNESP]; Drigo Filho, Elso [UNESP] (Springer Nature, 2021)
Abstract: The potential curve for a confined He 2 dimer is computed using the variational method. The approach proposed here uses a trial function for the ground state composed of the Slater determinant with the orbitals proposed in a previous paper. These orbitals (bond and anti-bond) are given by a linear combination of atomic orbitals for a confined hydrogen atom. The dimer is confined in an impenetrable prolate spheroidal box. The density over the internuclear axis is also studied. The results found here indicate that the confinement changes the characteristic of the potential curve; for a weak confinement parameter (a larger box), the potential curve has a very shallow minimum; and for a strong confinement (a smaller box), the minimum becomes well-characterized. This behaviour indicates that spatial confinement can increase the bond between the atoms. GraphicAbstract: [Figure not available: see fulltext.]